Increased pathological complete response rate after a long-term neoadjuvant letrozole treatment in postmenopausal oestrogen and/or progesterone receptor-positive breast cancer - Allevi, G; Strina, C; Andreis, D; Zanoni, V; Bazzola, L; Bonardi, S; Foroni, C; Milani, M; Cappelletti, MR; Gussago, F; Aguggini, S; Giardini, R; et al. (2013)
Background: The objective of this study was to determine the optimal scheduling of 2.5 mg daily letrozole in neoadjuvant breast cancer patients to obtain pathological complete response (pathCR) and assess Ki-67 expression as an early predictor of response.Patients and methods:This single institution study comprised 120 oestrogen receptor (ER)-positive postmenopausal women with primary breast cancer (clinical stage ≥T2, N0-1), from three sequential cohorts (cohort A of 40, cohort B of 40 and cohort C of 40 patients, respectively) based on different duration of the neoadjuvant letrozole. Biological markers such as ER, progesterone receptor, HER2 and Ki-67 expression were tested at diagnosis and at definitive surgery.Results:A total of 89 patients (75.4%) achieved an objective response with 44 (37.3%) clinical CRs and 45 (38.1%) partial responses. The clinical CRs were significantly observed in cohort C (23 out of 40 patients, 57.5%) and B (16 out of 38 patients, 42.1%) compared with cohort A (5 out of 40 patients, 12.5%) (P-value for trend <0.001). Letrozole induced a similar significant reduction in Ki-67 index after treatment in all cohorts. The pathCR rate was significantly more frequent in cohort C (7 out of 40 patients, 17.5%) than in cohort A (1 out of 40 patients, 2.5%) and B (2 out of 40 patients, 5.0%) (P-value for trend <0.04).Conclusion:One-year neoadjuvant letrozole therapy leads to a higher pathCR rate and may be the optimal length of drug exposure. © 2013 Cancer Research UK. All rights reserved.